Power Spectral Analysis of Heart Rate Variability in Hypertensive Male - Tabassum, Rehnuma; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2011)
Background: Essential hypertension is associated with altered cardiovascular autonomic nerve function. Heart Rate Variability (HRV) analysis is an important tool for quantitative measurement of autonomic nerve activity. Objective: To assess the cardiac autonomic nerve function status in essential hypertension by analyzing power spectral measures of heart rate variability. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University between July 2008 and June 2009. Sixty male hypertensive patients with age range 40-60 years (group B) were enrolled from the Out Patient Department of Cardiology, BSMMU, Dhaka. Thirty age and sex matched apparently healthy normotensive subjects (group A) were studied as control, Hypertensive patients were further divided into group B1 consisting of 30 untreated patients on their 1st day of diagnosis and group B2 consisting of 30 patients under antihypertensive therapy. Power Spectral measures of Heart Rate Variability (HRV) such as total power, low frequency (LF) and high frequency power (HF) LH/HF ratio were assessed by a digital Polygraph. For statistical analysis, Independent sample t-test, One-way ANOVA test and Pearson’s correlation coefficient test were done as applicable. Results: Mean TP, LF, HF and HF norm was significantly (p<0.001) lower and LF/HF ratio and LF norm were significantly (p<0.001) higher in both untreated and treated hypertensive patients compared to those of normotensive subjects. Again, significant differences of LF norm and HF norm and LF/HF ratio were found between the two hypertensive groups. The LF/HF ratio and LF norm were positively and HF norm was negatively correlated with SBP and DBP in both the hypertensive groups. However, all these findings were more marked in untreated hypertensive patients than those of treated group. Conclusion: Sympathovagal balance in hypertensive patients is towards higher sympathetic and lower vagal modulation and effective treatment of the patients can return the balance towards normal. Key words: LF norm; HF norm; LF/HF ratio; hypertension DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8082 J Bangladesh Soc Physiol. 2011 June; 6(1): 32-38